2010
DOI: 10.3747/co.v17i3.494
|View full text |Cite
|
Sign up to set email alerts
|

Multimodality Breast Cancer Screening in Women with a Familial or Genetic Predisposition

Abstract: BackgroundWomen with a predisposition for breast cancer require a tailored screening program for early cancer detection. We evaluated the performance of mammography (mg), ultrasonography (us), and magnetic resonance imaging (mri) screening in these women. Patients and MethodsIn asymptomatic women either confirmed as BRCA1/2 carriers, or having a greater than 30% probability of being so as estimated by brcapro [Berry D, Parmigiani G. Duke spore (Specialized Program of Research Excellence) in Breast Cancer. 1999… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…The specificity of breast examination in our study was consistent with other reports (range, 95.9‒99.3% 8,9,12,13 5‐8 ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The specificity of breast examination in our study was consistent with other reports (range, 95.9‒99.3% 8,9,12,13 5‐8 ).…”
Section: Discussionsupporting
confidence: 93%
“…The reported performance of breast examination for detecting breast cancer is highly variable; in women at high risk, sensitivity ranges between 0 and 64.1% and specificity between 95.9% and 99.3% 5‐16 . Its reported sensitivity in women with BRCA1/2 mutations is 0–13% 5‐8 …”
mentioning
confidence: 99%
“…As outlined in the Introduction, contrast-enhanced breast MRI has been recognised as a valuable screening tool in women at high BC risk. From 2000 to 2015, several studies reported a large superiority of MRI versus mammography (in some studies also versus ultrasound) in women with hereditary BC predisposition [ 58 72 ] (Table 1 ). Ten studies, 15 papers, over 6000 women enrolled, near 19,000 rounds.…”
Section: The Case For Breast Mri For High-risk Screeningmentioning
confidence: 99%
“…Earlier this year in Current Oncology, Trop and colleagues added new information to support the claim that screening with magnetic resonance imaging (mri) for breast cancer is superior-in terms of sensitivityto routine mammography 1 . This news should be welcome to women who are found to carry a mutation in the BRCA1 or BRCA2 gene and should encourage more women to undergo genetic testing.…”
Section: Sa Narod MDmentioning
confidence: 99%